Pemanfaatan Excel Dalam Penyusunan Laporan Keuangan Sederhana Pada Usaha Sablon Di Desa Santong Kecamatan Kayangan Kabupaten Lombok Utara - Lukman Effendy; Zuhrotul Isnaini; Isnawati Isnawati (https://jurnal.fe.unram.ac.id/index.php/abdimas/about/privacy, 2023)
Financial reports have a very important role in the sustainability of an agency or organization. There is a lack of insight and understanding regarding modernization in financial reporting at the Makmur Abadi Printing Business and Langit Biru Printing, so direction and knowledge must be given to operate Microsoft Excel software in preparing simple financial reports. That way, service partners can make financial reports easily and practically. Not only that, to make it easier to remember the composition of financial reports, a simple financial report format was created that is concise and easy to understand so that what was originally recorded manually can be summarized more effectively and efficiently. This service activity is urgently carried out as a solution to this problem. This type of service activity is helping the printing business in Santong Village prepare simple financial reports using Microsoft Excel. The implementation method for this service activity is carried out using a simulation method to provide direct experience to the owners of the Makmur Abadi Printing Business and other screen printing entrepreneurs in Santong Village in recording financial reports. Apart from that, the question-and-answer method and mentoring are used during the process of preparing financial statements. The result of this service is the design of an accounting system using Microsoft Excel. Service Partners can use examples of monthly profit and loss calculations resulting from the output of this service to be applied in preparing financial reports for the following months.